Management of stoma prolapse using polypropylene mesh strip: A novel and easy technique - Vishesh Jain; Nellai Krishnan; Prabudh Goel (Wolters Kluwer Medknow Publications, 2024)
Stomal prolapse is one of the most common complications of enterostoma. Stoma if persistent and significant often requires revision of stoma. The techniques described often require laparotomy with resection or internal fixation of the bowel. Such procedures may make further laparotomy more difficult. We herein describe the use of a relatively simple procedure for the correction of stomal prolapse.